Uncoupling protein 2 regulates daily rhythms of insulin secretion capacity in MIN6 cells and isolated islets from male mice - Nivedita Seshadri; Michael E. Jonasson; Kristin L. Hunt; Bo Xiang; Steven Cooper; Michael B. Wheeler; Vernon W. Dolinsky; Christine A. Doucette (Elsevier, 2017)
Objective: Upregulation of uncoupling protein 2 (UCP2) is associated with impaired glucose-stimulated insulin secretion (GSIS), which is thought to be an important contributor to pathological β cell failure in obesity and type 2 diabetes (T2D); however, the physiological function of UCP2 in the β cell remains undefined. It has been suggested, but not yet tested, that UCP2 plays a physiological role in β cells by coordinating insulin secretion capacity with anticipated fluctuating nutrient supply, such that upregulation of UCP2 in the inactive/fasted state inhibits GSIS as a mechanism to prevent hypoglycemia. Therefore, we hypothesized that daily cycles of GSIS capacity are dependent on rhythmic and predictable patterns of Ucp2 gene expression such that low Ucp2 in the active/fed phase promotes maximal GSIS capacity, whereas elevated Ucp2 expression in the inactive/fasted phase supresses GSIS capacity. We further hypothesized that rhythmic Ucp2 expression is required for the maintenance of glucose tolerance over the 24 h cycle. Methods: We used synchronized MIN6 clonal β cells and isolated mouse islets from wild type (C57BL6) and mice with β cell knockout of Ucp2 (Ucp2-βKO; and respective Ins2-cre controls) to determine the endogenous expression pattern of Ucp2 over 24 h and its impact on GSIS capacity and glucose tolerance over 24 h. Results: A dynamic pattern of Ucp2 mRNA expression was observed in synchronized MIN6 cells, which showed a reciprocal relationship with GSIS capacity in a time-of-day-specific manner. GSIS capacity was suppressed in islets isolated from wild type and control mice during the light/inactive phase of the daily cycle; a suppression that was dependent on Ucp2 in the β cell and was lost in islets isolated from Ucp2-βKO mice or wild type islets treated with a UCP2 inhibitor. Finally, suppression of GSIS capacity by UCP2 in the light phase was required for the maintenance of normal patterns of glucose tolerance. Conclusions: Our study suggests that Ucp2/UCP2 in the β cell is part of an important, endogenous, metabolic regulator that controls the temporal capacity of GSIS over the course of the day/night cycle, which, in turn, regulates time-of-day glucose tolerance. Targeting Ucp2/UCP2 as a therapeutic in type 2 diabetes or any other metabolic condition must take into account the rhythmic nature of its expression and its impact on glucose tolerance over 24 h, specifically during the inactive/fasted phase.